Penggunaan Crossword-puzzle dan Yes/No Questions dalam pengajaran Parts of Body dan Health Problems pada Siswa SMK Kesehatan - Susandi, Ni Kadek Ary; Rusanti, Putu; Galuh Wismadewi, I Gusti Agung; Suryati, Ni Wayan Novi (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
At the vocational high school level in Indonesia, English language teaching is still general with minimal ESP additions, so it is not enough to equip students to be able to communicate using English according to their future field of work. English material in Health Vocational High Schools is less focused on the specific needs of the health sector. The lack of variety of fun learning activities makes students less interested and motivated to learn English, especially related to health terms. Therefore, innovative and comprehensive learning is needed with materials that are appropriate for the needs of students as prospective nursing assistants. One of them is by utilizing crossword puzzle games and yes/no questions. The programs that have been implemented have proven effective in increasing students' interest in learning and their understanding of vocabulary related to body parts and health problems. This shows that a fun and interactive approach can be a good solution in learning English in Health Vocational High Schools.